Episodic focus formulation in media scholars’ data interaction - Korkeamäki, Laura; Keskustalo, Heikki; Kumpulainen, Sanna (Information Research an international electronic journal, 2024)
Introduction. Focus formulation affects task information interaction and task performance. It has typically been conceptualised as one task stage in the overall task performance. Nevertheless, we take a different approach by studying focus formulation as an episodic phenomenon in the task process performance. Episodic focus formulation includes several focus formulation episodes during task performance processes that gradually lead to focus, but instead of considering the larger task, this happens during a subtask. The purpose of this study is to examine what is episodic focus formulation like in media scholars’ data interaction. Method. We interviewed twenty-five media scholars about their research processes and related interactions with their research data. Analysis. We examined focus formulation episodes as sense-making instances. We identified the focus formulation episodes from the interview data and analysed across them by annotating and categorizing. We analysed the episodic focus formulations by subtasks and then summarised over the subtasks to cover the whole data interaction. Results. We identified three subtasks, each with three episodic focus formulations. Summarising over the subtasks showed that episodic focus formulation in data interaction encompasses task focus, data focus and procedural focus formulation. Conclusions. This study has implications for theory development and for supporting data interaction.